PENGEMBANGAN PRODUK PROTOTIPE UI/UX WEBSITE EKSTRAKURIKULER BERBASIS FIGMA UNTUK MENINGKATKAN BRANDING DIGITAL SMA AL-HASRA KOTA DEPOK - Abdullah Muhajir; Firman Ardiansyah; Ariel Prama Yudha; Elisabeth Manik; Salshabila Sucy Ayu Ramadhania; Rayyan Muhammad Arrafi; Syarief Hidayatulloh; Muhamad Al Gadafi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The digital era demands that educational institutions, including SMA Al-Hasra Depok, utilize digital platforms to strengthen their institutional branding, particularly for extracurricular activities. Branding in the educational context is an effort to create a strong identity and can be achieved through a school website. A well-designed website can be a strategic digital promotion medium. This study aims to develop a UI/UX prototype for the SMA Al-Hasra extracurricular website using Figma to enhance its digital branding. The method used is a Research and Development (R&D) approach focusing on the prototype stage. The initial phase involved a necessity analysis to identify the need for varied and innovative digital materials. The design process involved using Figma, a tool known for its robust features and ability to create interactive prototypes. The results show that the developed prototype provides an aesthetic (UI) and easy-to-use (UX) solution that is expected to increase user satisfaction and create a positive image for the school. This development contributes to enhancing the overall quality of education (mutu pendidikan) through modern digital management.